2007
DOI: 10.3354/dao073207
|View full text |Cite
|
Sign up to set email alerts
|

Ichthyobodo hippoglossi n. sp. (Kinetoplastea: Prokinetoplastida: Ichthyobodonidae fam. nov.), an ectoparasitic flagellate infecting farmed Atlantic halibut Hippoglossus hippoglossus

Abstract: Diseased Atlantic halibut Hippoglossus hippoglossus juveniles from a hatchery in western Norway showed gill and skin infections with an Ichthyobodo species. Genus Ichthyobodo contains a single valid species, I. necator, a parasite originally described from the skin and fins of a salmonid fish in freshwater. Many studies have identified this species from other hosts, but recent molecular evidence suggests that many Ichthyobodo spp. occur in both fresh-and seawater. We redescribe I. necator from Atlantic salmon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…Ichthyobodo spp. are reported from salmonids, cod and halibut (Isaksen et al, 2007;Karlsbakk et al, 2009; Rintamaki Kinnunen and Valtonen, 1997) and pose a major threat to both wild and farmed fish populations. The parasite is found on the skin of juvenile salmon in freshwater, and if left untreated can lead to mass mortalities (Poppe, 1999;Rintamaki Kinnunen and Valtonen, 1997).…”
Section: Ichthyobodo Sppmentioning
confidence: 99%
“…Ichthyobodo spp. are reported from salmonids, cod and halibut (Isaksen et al, 2007;Karlsbakk et al, 2009; Rintamaki Kinnunen and Valtonen, 1997) and pose a major threat to both wild and farmed fish populations. The parasite is found on the skin of juvenile salmon in freshwater, and if left untreated can lead to mass mortalities (Poppe, 1999;Rintamaki Kinnunen and Valtonen, 1997).…”
Section: Ichthyobodo Sppmentioning
confidence: 99%
“…Callahan et al (2005) identified a complex of 9 different species with low host specificity, one of which was capable of infecting both marine and freshwater fish. A species of Ichthyobodo was reported from cod by Isaksen et al (2007). Clearly Ichthyobodo is a potentially serious pathogen in cod mariculture.…”
Section: Protozoamentioning
confidence: 99%
“…This hampers the acquisition of epizootiological information about the actual Ichthyobodo species involved. Farmed Atlantic salmon in Norway may be infected with I. necator s.s. (Isaksen et al 2007) and Ichthyobodo sp. II sensu Todal et al (2004).…”
Section: Discussionmentioning
confidence: 98%
“…comprises several Ichthyobodo spp. that may be discerned by their small subunit ribosomal DNA (SSU rDNA) sequences (Todal et al 2004, Callahan et al 2005, Isaksen et al 2007). In a previous study, we delimited I. necator (sensu stricto, s.s.) as a parasite thus far only known to infect freshwater fishes in Europe (Isaksen et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation